2017
DOI: 10.1073/pnas.1714183114
|View full text |Cite
|
Sign up to set email alerts
|

Thin myelin sheaths as the hallmark of remyelination persist over time and preserve axon function

Abstract: The presence of thin myelin sheaths in the adult CNS is recognized as a marker of remyelination, although the reason there is not a recovery from demyelination to normal myelin sheath thickness remains unknown. Remyelination is the default pathway after myelin loss in all mammalian species, in both naturally occurring and experimental disease. However, there remains uncertainty about whether these thin sheaths thicken with time and whether they remain viable for extended periods. We provide two lines of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…Around 40% of axons of all calibers had thin myelin sheaths, as previously reported (1). The pattern seen on recovery, which is a mixture of mature and remyelinated myelin sheaths, persisted over time (30). In one animal examined 2.5 y after termination of the irradiated diet, the pattern of mixed distribution of remyelinated and mature myelin sheaths remained in the ventral column ( Fig.…”
Section: Scattered Demyelination and Remyelination Lead To A MIX Of Rsupporting
confidence: 80%
See 1 more Smart Citation
“…Around 40% of axons of all calibers had thin myelin sheaths, as previously reported (1). The pattern seen on recovery, which is a mixture of mature and remyelinated myelin sheaths, persisted over time (30). In one animal examined 2.5 y after termination of the irradiated diet, the pattern of mixed distribution of remyelinated and mature myelin sheaths remained in the ventral column ( Fig.…”
Section: Scattered Demyelination and Remyelination Lead To A MIX Of Rsupporting
confidence: 80%
“…1). Examination of longitudinal sections through these areas of white matter showed that there were many short internodes on thinly myelinated (remyelinated) axons (30). In contrast to the lateral and ventral column, remyelination of the dorsal column resulted in large areas of homogeneously thin myelin sheaths ( Fig.…”
Section: Scattered Demyelination and Remyelination Lead To A MIX Of Rmentioning
confidence: 98%
“…This is supported by the significant albeit incomplete recovery of electrophysiological properties over the affected wrist segment following surgical decompression. Persistence of thin myelin sheets after remyelination as shown in experimental models 26,27 may account for the continuing conduction slowing.…”
Section: Discussionmentioning
confidence: 92%
“…Myelin sheath thickness is a parameter of considerable interest in neuroscience. It is an important factor in signal conduction velocity [41] and may be used as a marker for disease [42]. Together with the axon diameter it determines the g-ratio.…”
Section: Discussionmentioning
confidence: 99%